Chronic kidney disease and anemia: application of ferrous bisglycinate chelate for correction of iron deficiency in patients with chronic kidney disease - Ivanov, D.D. (KIDNEYS, 2021)
Anemia is a component of chronic kidney disease, having erythropoietin- and iron deficiency nature. 2012 KDIGO guidelines determine anemia as a hemoglobin concentration < 120 g/l in women and < 130 g/l in men. An iron deficiency occurs in more than 50 % of patients with non-dialysis-dependent chronic kidney disease and in the majority of patients receiving dialysis. For the diagnosis of iron deficiency, the value of serum ferritin level and transferrin saturation are used. Reduction of any of these indicators is the basis for hemoglobin correction by iron compounds. Iron deficiency increases with existing inflammation, its need increases with erythropoietin treatment. Among oral molecules, bivalent iron salts or those that are not hydrolyzed have the best absorption profile, high bioavailability and well regulate iron deficiency. The article considers Tecnofer as an example of compounds with certain advantages for the iron deficiency correction in anemia in patients with chronic kidney disease.